TRADITIONAL CONFLICT AND ITS INTERVENTIONS - Muhlis, Muhlis (IAIN Walisongo Semarang, 2013)
AbstractThe Ngali-Renda conflict is habituated. It has taken for years. It has grown in itsseverity. It is not the case that the people of Ngali and Renda and the government donothing in dealing with the conflict. However, the conflict is still there and waiting itstrigger to appear. This research is significant in that it analyzes the traditionalfactors and interventions of the conflict. Applying qualitative research and historical,socio-cultural and phenomenological approaches showed that the Ngali-Rendaconflict transformed from ndempa (empty-handed fighting) to lewa (armedfighting). Ndempa implied the spirit of honesty, openness and patriotism. It occurredevery year in rest period of cultivation and took one or two month. Although ndempawas kapoda ade (serious and violent), it was kadihi ade (no intention to do harm)and for play and pleasure. On the contrary, lewa was more violent and causedcasualties because the fighters used big knifes, arrows and firearms.***Konflik Ngali-Renda merupakan konflik yang sudah biasa terjadi. Konflik inimerupakan konflik kekerasan. Masyarakat Ngali-renda maupun pemerintah telahberupaya untuk mengatasi konflik tersebut, namun belum menampakkan hasil.Penelitian ini memiliki ati penting untuk melihat faktor-faktor tradisional danpenanganan konflik yang telah dilakukan. Tampak dalam penelitian ini bahwakonflik Ngali-Renda merupakan transformasi konflik dari ndempa (perkelahiantanpa senjata) menjadi lewa (perkelahian dengan senjata). Ndempa memilikimakna semangat kejujuran, keterbukaan, dan patriotisme. Tradisi ini merupakantradisi tahunan, yang dilakukan setelah musim tanam dan berlangsung selamasatu hingga dua bulan. Walaupun ndempa disebut kapoda ade (sungguh-sungguhdan keras) namun kadihe ade (tidak berniat untuk menyakiti), dan hanya untuktujuan permainan dan kesenangan. Sementara lewa lebih keras dan menyebabkankorban luka karena pelaku menggunakan pedang, panah, serta senjata api.Keywords: Ngali-Renda, ndempa, Lewa, conflict, violence